Case Report: Dilemma To Save Or Not To Save A Tooth - Yap, Yee Woo; Mohd Ali, Azillah (IIUM Medical Journal Malaysia, 2017)
Introduction: Dentigerous cyst is the most common odontogenic cysts that are associated with the crowns of permanent teeth. Treatment modalities normally include enucleation or marsupialization of the cyst. However, currently there are no standard assessment criteria to dictate which kind of treatment for certain cases. The purpose of this report is to describe the successful outcome of conservative surgical management of a large dentigerous cyst associated with an unerupted right maxillary permanent canine in an 8-year-old boy. The cyst was enucleated partially but leaving the cystic lining surrounding the unerupted canine in order to preserve the tooth. 3-year follow up revealed good healing with significant root formation and tooth eruption.